Prenatal and Postnatal Assessment in Rabbits with Evacetrapib: A Cholesteryl Ester Transfer Protein Inhibitor. Issue 7 (31st March 2017) - Breslin, William J.; Hilbish, Kim G.; Cannady, Ellen A.; Edwards, Tammy L.
Abstract : Background: Evacetrapib, a potent and selective inhibitor of cholesteryl ester transfer protein (CETP), was under development for the treatment of cardiovascular (CV) disease. The purpose of this pre‐postnatal study in rabbits was to evaluate the effects of evacetrapib on pregnancy, parturition, and lactation of the maternal animals and on the growth, viability, development, and reproductive performance of the first filial (F1) offspring. The rabbit is considered a relevant species for toxicity testing with evacetrapib as it demonstrates significant CETP expression, whereas mice and rats do not express significant levels of CETP. Methods: Evacetrapib was administered daily by oral gavage from gestation day (GD) 7 through lactation day (LD) 41 at dose levels of 0, 10, 30, and 100 mg/kg/day. Results: There were no adverse effects on maternal survival, clinical signs, gestation length, parturition, and litter size. There were no effects on F1 clinical observations, body weight, sexual maturation, conditioned eye blink, functional observational battery, or pathology findings. Treatment‐related decreases in F1 postnatal survival and equivocal reductions in F1 mating, fertility, and copulation/conception indices without changes in sperm parameters or pathology of reproductive organs were noted in F1 animals. Conclusions: The maternal no observed adverse effect level (NOAEL) after evacetrapib administration in female rabbits was 100 mg/kg/day. Based on the decreased F1 postnatal survival and equivocal changes in F1 fertility, the NOAEL for F1 neonatal developmental was 30 mg/kg/day. Birth Defects Research 109:486–496, 2017.© 2017 Wiley Periodicals, Inc.